2012
DOI: 10.1002/cbic.201200145
|View full text |Cite
|
Sign up to set email alerts
|

DNA Microarray Expression Analysis of Baicalin‐Induced Differentiation of C17.2 Neural Stem Cells

Abstract: Identifying baicalin-regulated genes for neuronal differentiation: Baicalin is a potent neuronal-differentiation-inducing compound. This study explored the gene expression regulated through baicalin-induced differentiation of C17.2 neural stem cells by using a DNA microarray followed by qPCR validation. The expression of 15 genes was significantly regulated among the 58 differentially expressed genes important for nervous system development and function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…A few studies have reported the differentiation potential of some herbal extracts on different types of stem cells (Udalamaththa et al, 2016). Additionally, several plant extracts and their active components showed potential effects in neuronal differentiation and proliferation, like phytochemicals from Butea superba in stem cells (Arai et al, 2013), flavonoid component from Scutellaria baicalensis in C17.2 cells (Li et al, 2012), acetic acid extract of Mucuna gigantea in bone marrow-derived hMSCs (Kongros et al, 2012), Salvia miltiorrhiza extract on Wharton jelly derived hMSCs (Ma et al, 2005). However, to our knowledge, there is no study to date reporting the effect of any natural compounds on hAECs differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have reported the differentiation potential of some herbal extracts on different types of stem cells (Udalamaththa et al, 2016). Additionally, several plant extracts and their active components showed potential effects in neuronal differentiation and proliferation, like phytochemicals from Butea superba in stem cells (Arai et al, 2013), flavonoid component from Scutellaria baicalensis in C17.2 cells (Li et al, 2012), acetic acid extract of Mucuna gigantea in bone marrow-derived hMSCs (Kongros et al, 2012), Salvia miltiorrhiza extract on Wharton jelly derived hMSCs (Ma et al, 2005). However, to our knowledge, there is no study to date reporting the effect of any natural compounds on hAECs differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Baicalin is a flavonoid found in the Chinese herb Scutellaria baicalensis. Previous studies had demonstrated that baicalin could promote the neural differentiation of human iPS cells, immortalized mouse C17.2 neural progenitor cells, and rat embryonic cortical NSCs [11][12][13]. Interestingly, baicalin improved neural differentiation but inhibited glial formation [12].…”
Section: Neural Differentiationmentioning
confidence: 97%
“…Previous studies had demonstrated that baicalin could promote the neural differentiation of human iPS cells, immortalized mouse C17.2 neural progenitor cells, and rat embryonic cortical NSCs [11][12][13]. Interestingly, baicalin improved neural differentiation but inhibited glial formation [12]. Many other traditional Chinese medical herbal ingredients also have the ability to differentiate stem cells into specialized cell subtypes.…”
Section: Neural Differentiationmentioning
confidence: 99%
“…Baicalin can stimulate differentiation of C17.2 NSCs by activating Erk1/2 (Li et al, 2011), which controls neural differentiation-related gene expression. Under the effects of Baicalin, the expression levels of NeuroD2, Ngn1, and Ngn2 mRNA are upregulated (Li M. et al, 2012) (Figure 4). Neurogenic , 2019).…”
Section: Baicalin and Neural Stem Cellsmentioning
confidence: 99%